Exploring efficacy in personal constraint negotiation: An ethnography of mountaineering tourists. (December 2019) - Doran, Adele; Pomfret, Gill
Limited work has explored the relationship between efficacy and personal constraint negotiation for adventure tourists, yet efficacy is pivotal to successful activity participation as it influences people's perceived ability to cope with constraints, and their decision to use negotiation strategies. This article explores these themes with participants of a commercially organised mountaineering expedition. Phenomenology-based ethnography was adopted to appreciate the social and cultural mountaineering setting from an emic perspective. Ethnography is already being used to understand adventure participation, yet there is considerable scope to employ it further through researchers immersing themselves into the experience. The findings capture the interaction between the ethnographer and the group members, and provide an embodied account using their lived experiences. Findings reveal that personal mountaineering skills, personal fitness, altitude sickness and fatigue were the four key types of personal constraint. Self-efficacy, negotiation-efficacy and other factors, such as hardiness and motivation, influenced the effectiveness of negotiation strategies. Training, rest days, personal health and positive self-talk were negotiation strategies. A conceptual model illustrates these results and demonstrates the interplay between efficacy and the personal constraint negotiation journey for led mountaineers.